A BODIPY/pyrene-based chemodosimetric fluorescent chemosensor for selective sensing of hydrazine in the gas and aqueous solution state and its imaging in living cells1. Issue 72 (6th August 2015) - Mahapatra, Ajit Kumar; Maji, Rajkishor; Maiti, Kalipada; Manna, Saikat Kumar; Mondal, Sanchita; Ali, Syed Samim; Manna, Srimanta; Sahoo, Prithidipa; Mandal, Sukhendu; Uddin, Md Raihan; Mandal, Debasish
<x xml:space="preserve">Abstract</x> A BODIPY-based pyrenebutyrate-linked (BPB) chromogenic and fluorogenic probe was synthesized and characterized for the specific detection of hydrazine.